Media portrayal of elite athletes with disability – a systematic review. Issue 4 (13th February 2019) - Rees, Leanne; Robinson, Priscilla; Shields, Nora
Abstract: Background: The media plays an important role in shaping society's beliefs about disability and sport. The aim of this systematic review is to identify how elite athletes with disability are portrayed in the media. Method: Six electronic databases were searched from 2001 to March 2017 for quantitative or qualitative content analysis of media coverage of elite athletes with disability: SportsDiscus, CINAHL, PsychInfo, Medline 1996-, Embase, and Proquest. Quality assessment and data extraction were performed by two independent assessors. Results: Seventeen moderate quality articles were included. Six themes emerged from the data such as frequency of articles and photos about elite athletes with disability; athlete gender; athlete nationality; disability; athleticism; and Olympic Games versus Paralympic Games. Our results show that elite athletes with disability are less visible in the media than their nondisabled counterparts; female athletes received less coverage than male; the media favored domestic athletes and certain types of disability; and, although there was a focus on athleticism, this was underpinned by a "supercrip" narrative and a medicalised description of disability. Conclusion: Although there has been a positive shift in the narrative around elite athletes with disability in media, relative absence and differing portrayal is present. Considering the power of media shaping society's perceptions of disability, further investigation is warranted. Implications for Rehabilitation: Media has a role in how elite athletes with disability are portrayed and consequently perceived by the public. Elite athletes with disability rarely feature in media. Images of disability are minimized, and certain types of disabilities are favored. An athletic narrative is emerging; however, a medicalised description of athletes remains, shifting the focus from athleticism. "Supercrip" and "Superhuman" terms are commonly used, but may negatively impact the broader disability community.